2002
DOI: 10.1128/cdli.9.1.132-137.2002
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Challenge Stimulates Formation of Arachidonic Acid Metabolites by Human Keratinocytes and Neutrophils In Vitro

Abstract: Although the interactions of bacteria with keratinocytes induce the synthesis of various mediators, the capability of epithelial cells to form arachidonic acid mediators has not been studied, and therefore the first part of this study was initiated. The complex mixture of epithelium-derived mediators suggests that chemoattraction is not their only effect on neutrophils and that they may also affect neutrophil mediator synthesis. The effect of epithelium-derived mediators on neutrophil eicosanoide synthesis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…It has been reported that components of the arachidonic acid cascade, the leukotrienes, synthesized in epithelial cells, are potent inducers of inflammation after bacterial challenge (8). The results of the present study confirm this and show the induction of a key enzyme for the leukotriene B 4 synthesis – 5‐LO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that components of the arachidonic acid cascade, the leukotrienes, synthesized in epithelial cells, are potent inducers of inflammation after bacterial challenge (8). The results of the present study confirm this and show the induction of a key enzyme for the leukotriene B 4 synthesis – 5‐LO.…”
Section: Resultsmentioning
confidence: 99%
“…Various links have been revealed referring to interactions between the innate and the acquired immune systems, including antimicrobial peptides and regulatory enzymes of the arachidonic acid cascade (8, 26). Epithelial cells upon induction secrete both IL‐8 and leukotriene B 4 in response to A. actinomycetemcomitans (8). In contrast to IL‐8, the enzyme 5‐LO of the arachidonic acid cascade was upregulated by short‐time growth of biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…EP4 is involved in skin inflammation. It has been suggested that PGE 2 is upregulated within antigen-exposed skin (Ruzicka and Printz, 1982;Eberhard et al, 2002). Kabashima et al (2003) demonstrated that PGE 2 promoted skin immune responses by enhancing the migration and maturation of Langerhans cells through EP4 signaling.…”
Section: +mentioning
confidence: 99%
“…17 Multiple cells typically found in the wound bed are capable of eicosanoid synthesis. 3,8,18,19 Bacteria can induce synthesis of various eicosanoids, 20 although their contribution in acute and chronic wounds remains to be further studied. Free radical-induced conversion of AA into the isoprostanes, 21 which serve as prostaglandin analogs, augments the eicosanoid levels in the wound.…”
Section: Discussion Eicosanoids In the Wound Microenvironmentmentioning
confidence: 99%